Evaluation of an evidence-based contraceptive advice line used to support contraceptive provision in primary care. Issue 4 (1st October 2010) - Graham, Okunyomibo; Aung, Soe Nyunt; Guthrie, Kate
Abstract : Background: An e-contraceptive advice line (contraceptionadvice.GP@hullpct.nhs) was set up by our unit to support contraceptive provision in primary care. This advice line was for general practitioners (GPs) initially and was then extended to certain pharmacists. All queries were to be answered within 24 hours. A similar e-advice line on emergency contraception for patients seeking advice had been successful in the USA and South Africa. Methods: Our aim was to evaluate the contraceptive advice line using standards developed at its inception. A retrospective audit of the queries received by the contraceptive advice line between January and September 2009 was conducted. Results: Sixty-seven queries were received from 30 GPs, nine from practice nurses and none from pharmacists. Some 61% of the queries were answered within 24 hours and 85% were answered within 72 hours; 90% were within the advice line guidelines. Conclusions: The e-mail advice line is a useful, low-cost, well-received support service for GPs. This model could be adopted by other areas wishing to increase contraceptive access in primary care.